2021
DOI: 10.1021/acs.molpharmaceut.1c00565
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Self-Assembled Rhein–Doxorubicin Nanogel Targeting Mitochondria and Investigation on Its Antihepatoma Activity

Abstract: Mitochondria are involved in the regulation of apoptosis, making them a promising target for the development of new anticancer drugs. Doxorubicin (DOX), a chemotherapeutic drug, can induce reactive oxygen species (ROS)-mediated apoptosis, improving its anticancer effects. Herein, Rhein, an active ingredient in rhubarb, with the capability of self-assembly and mitochondrial targeting, was used in conjunction with DOX to form efficient nanomaterials (Rhein–DOX nanogel) capable of sustained drug release. It was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Natural product rhein‐based ruthenium‐arene complex has been reported in our recent study, where rhein would facilitate the complex to localize in mitochondria and generate synthetic lethality behavior after conjugation to the Ru‐arene component in vivo [24] . Previous pharmacologic study indicated that rhein could target mitochondria via binding to a variety of molecules on the mitochondrial membrane and induce the pathological opening of the mitochondrial permeability transition pore (mPTP) [25, 26] . Inspired by this result, a novel rhein‐functionalized mitochondria‐targeting cyclometalated iridium(III) complex Ir‐Rhein (see Figure 1) was successfully synthesized in this work.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Natural product rhein‐based ruthenium‐arene complex has been reported in our recent study, where rhein would facilitate the complex to localize in mitochondria and generate synthetic lethality behavior after conjugation to the Ru‐arene component in vivo [24] . Previous pharmacologic study indicated that rhein could target mitochondria via binding to a variety of molecules on the mitochondrial membrane and induce the pathological opening of the mitochondrial permeability transition pore (mPTP) [25, 26] . Inspired by this result, a novel rhein‐functionalized mitochondria‐targeting cyclometalated iridium(III) complex Ir‐Rhein (see Figure 1) was successfully synthesized in this work.…”
Section: Introductionmentioning
confidence: 91%
“…[24] Previous pharmacologic study indicated that rhein could target mitochondria via binding to a variety of molecules on the mitochondrial membrane and induce the pathological opening of the mitochondrial permeability transition pore (mPTP). [25,26] Inspired by this result, a novel rhein-functionalized mitochondria-targeting cyclometalated iridium(III) complex Ir-Rhein (see Figure 1) was successfully synthesized in this work. Compared with the rhein-free cyclometalated iridium-(III) complex Ir-NH 2 (33.6 % accumulation in mitochondria), the mitochondrial occupation of complex Ir-Rhein in the total cellular uptake was elevated to 71.3 %, which demonstrated the strong mitochondria-targeting capability of rhein.…”
Section: Introductionmentioning
confidence: 96%
“…Tumor cell mitochondria are known to have higher levels of endogenous reactive oxygen species (ROS). 132 In the conjugate of the polymer and the cytotoxic peptide KLAK, the cleavage of the thioketal occurs under the trigger of ROS. This results in the destruction of the hydrophilic PEG and the breaking of the hydrophilic/hydrophobic balance.…”
Section: Self-assemblymentioning
confidence: 99%
“…Notably, a thioketal linkage was introduced to conjugate linoleic acid (LA) and gemcitabine into a GEM prodrug (LA-GEM). Second, LA-GEM and Rh were then self-assembled in water, together with the commercialized amphiphilic polymer DSPE-PEG 2k in the outer layer of nanoparticles, to enhance stability and long circulation of RP-NPs. , Based on the characteristics of the aforementioned materials, it could be speculatively assumed that the RP-NPs was a self-assembling system with hydrogen bonding, π–π stacking interactions, and hydrophobic interactions acting as the primary driving forces . Third, a HeLa tumor-bearing mice model was constructed.…”
Section: Introductionmentioning
confidence: 99%
“…51,52 Based on the characteristics of the aforementioned materials, it could be speculatively assumed that the RP-NPs was a self-assembling system with hydrogen bonding, π−π stacking interactions, and hydrophobic interactions acting as the primary driving forces. 53 Third, a HeLa tumor-bearing mice model was constructed. Upon US, the permeability of the tumor was increased, and the hypoxia state of the tumor was initially improved.…”
Section: ■ Introductionmentioning
confidence: 99%